The Emergent Properties of the Opera Genre in the Contemporary Musical Context (Música Hodie, 2024)
The purpose of this study is to reveal the emergent properties of the opera genre in the context of the development of contemporary music art. The methodological framework is based on general scientific and special methods, including analysis and synthesis, a historical and systematic approach to the study of the opera genre in a contemporary musical context. The findings of this study suggest that the properties of the opera genre under consideration include both traditions and new trends, such as the mass culture of music, an emphasis on the visual element of perception, a stronger entertainment function, the search for new forms of performance and the synthesis of different musical phenomena in opera art. Emergent properties in the opera genre are considered from various scientific perspectives, and various beliefs and statements of leading educators, musicians and scientists are compared and analysed. The practical significance of the study lies in developing of the modern direction of opera poetics theory and considering the theory of contemporary opera interpretation as a separate branch of contemporary performing art. This is related to the uniqueness and semantic palette of the opera variety, which helps to identify new emergent properties of the genre in line with contemporary traditions. The materials of the study can be used in the preparation of lectures on the history and theory of performing arts, dramatic theory of the opera genre, culturology, methodological work and opera studies in higher music education in Ukraine.